Verifierande prototyptest av integrerat elektrohydrauliskt drivsystem - Sjödin, Erik (2010)
Seeing the increased competition from electromechanical drives in the market segment for drives under 100 kW Hägglunds Drives AB submitted to Luleå Tekniska Universitet and the SIRIUS course a project to design and produce a prototype for a new and innovative integrated electrohydraulic drive system. This resulted in a working prototype being delivered by a group of students to Hägglunds Drives AB in the spring of 2009. This thesis covers the testing and verification of this prototype. The testing was carried out in the hydraulics laboratory at Hägglunds Drives AB facility in Mellansel, Sweden. In the testing energy efficiency both overall and on component level, the effects during startup from room temperature with the relatively high viscosity hydraulic fluid used, frequency converter characteristics, the need for cooling and performance were studied. Additionally a theoretical investigation into frequency converters was done. The results of the thesis show that the prototype works as intended, but more testing remains to be done before it can be considered a marketable product. Cooling for instance has been shown to be a much smaller issue than was thought during the design and production of the prototype, this would make it possible to use a lower working temperature for the hydraulic fluid as the large temperature difference to the surroundings is not necessary to achieve the required heat dissipation. Also the operational viscosity of the fluid can be considered to be higher than optimal and to cause a narrow span of possible operational temperature that will allow operation at full speed without encountering cavitation. The testing showed that the goals and requirements for efficiency has been met, as the prototype delivers >80% overall efficiency over a large part of its operational range and a peak overall efficiency of 83,4%. In a comparison with traditional systems using displacement control rather than frequency control the prototype system fares well with higher efficiency when run at other ...